PERAN PENANDA MOLEKULER PADA TERAPI GLIOMA - Malueka, Rusdy Ghazali; Yudiyanta, Yudiyanta; Asmedi, Ahmad (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2018)
ROLE OF MOLLECULAR MARKER IN GLIOMA THERAPYABSTRACTGliomas are the most common primary Central Nervouus System (CNS) tumors in adults. Nowdays, glioma classification has been changed from morphological based to molecular based classification. Isositrat dehydrogenase (IDH) muttion gene, chromosome 1p19q codeletion, O6-methylguanine-DNA-methyltransferase (MGMT) promoter methylation, epidermal growth factor receptor (EGFR) amplification, and vascular endothelial growth factor (VEGF) expression play important role in glioma management. These markers are important to be identified to help the diagnosis, determine the prognosis, predict the success of therapy, and develop targeted therapy and chemotherapy of glioma.IDH 1 and 2 gene mutation correlate with better outcome. 1p19q chromosome codeletion also a good prognosis indicator and strong predictor of chemosensitivity. MGMT gene expression level and methylation promoter gene status has a predictive value for glioblastoma patients who are treated with alkylation treatment, such as temozlamide. EGFR gene mutation correlates with aggressiveness and poor prognosis. VEGF over-expression is also comparable with the increasing stage of tumor. Clinical trial show promising therapeutic and safety for patients treated with anti-VEGF therapy, such as bevacizumab.Keywords: Chemotherapy, glioma, molecular marker, targeted therapyABSTRAKGlioma adalah tumor primer susunan saraf pusat (SSP) yang paling umum pada orang dewasa. Klasifikasi glioma saat ini beralih dari pedoman berbasis morfologi ke kriteria molekuler. Terdapat beberapa penanda (marker) molekuler yang berperan pada glioma, yaitu mutasi gen isositrat dehidrogenase (IDH), kodelesi kromosom 1p19q, metilasi promotor O6-metilguanin-DNA-metiltransferase (MGMT), amplifikasi epidermal growth factor receptor (EGFR), serta ekspresi vascular endothelial growth factor (VEGF). Hal ini penting untuk diidentifikasi untuk membantu diagnosis, menentukan prognosis, memprediksi keberhasilan terapi, serta untuk pengembangan terapi target dan kemoterapi.Adanya mutasi pada gen IDH 1 dan 2 berkaitan dengan prognosis yang lebih baik. Demikian pula kodelesi kromosom 1p19q merupakan indikator prognosis yang baik dan prediktor kuat kemosensitivitas. Tingkat ekspresi dan status metilasi promotor gen MGMT memiliki nilai prediktif pada pasien glioblastoma yang diobati dengan obat alkilasi, seperti temozolomid. Mutasi gen EGFR berkaitan dengan agresivitas dan prognosis yang buruk. Demikian pula over- ekspresi VEGF pada glioma sebanding dengan peningkatan derajat tumor. Uji klinik menunjukkan manfaat terapeutik serta keamanan yang sangat menjanjikan bagi pasien dengan terapi anti-VEGF, seperti bevacizumab.Kata kunci: Glioma, kemoterapi, penanda molekuler, terapi target